The Effect of Selenium on Changes in Thyroid Hormone-Related Deiodinase Enzyme Levels - Ercan BABUR; Umut BAKKALOĞLU; Cem SÜER; Nurcan DURSUN (Ahi Evran Medical Journal, 2022)
Purpose: The aim of this study is to investigate the effect of selenium on thyroid hormone-related deiodinase enzyme levels. Materials and Methods: The experiments were carried out on adult male Wistar rats aged 2 months. In total, 32 rats were used in the study. The rats were divided into 4 groups; control (Control, n=8, saline was applied), hypothyroid (6-n-propyl thiouracil (Ptu), n=8, 1mg/kg/day Ptu), hypothyroid+sodium selenite (Sena, n=8, Ptu+0.5mg/kg/day sodium selenite) and hypothyroid+seleno-L- methionine (Semet, n=8, Ptu+0.7mg/kg/day seleno-L-methionine) group. All drugs were administered with gastric gavage technique for 21 days. After the experiment, the blood samples taken from the rats sacrificed in a heparin tube were centrifuged at 4000 rpm for 5 minutes and their plasmas were separated. The hippocampus of the decapitated rats was removed. Hippocampus (deiodinase 2) DIO2 and (deiodinase 3) DIO3 protein levels were measured with western blot method. Se values on plasma and hippocampus were measured with inductively coupled plasma-mass spectrometry. Plasma-free Triiodothyronine (T3) and thyroxine (T4) levels were measured using a commercial ELISA kit. Results: Hippocampus DIO2 enzyme levels increased in the Ptu group compared to the control group (p=0.04) and DIO3 decreased (p=0.001). In the selenium (Se) supplemented groups, this difference in hypothyroidism disappeared. Conclusion: These findings suggest that selenium supplementation may improve thyroid hormone levels in patients with hypothyroidism.